The Moderating Role of the Sharia Supervisory Board in Detecting Fraud Opportunities in Islamic Banking Financial Reports Using the Fraud Hexagon Approach - Zainuddin; Muhammad Ikram. S; Wahyu Hasdi; Nurun Nuraini; Didin Purniawan (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of elements in the fraud hexagon on financial statement fraud in Islamic banking in Indonesia, as well as to evaluate the moderating role of the Sharia Supervisory Board. This study uses a quantitative approach with a panel data regression analysis method that includes 37 observations from the annual reports of Islamic commercial banks registered with the Financial Services Authority (OJK) during the 2019–2023 period. Financial statement fraud is detected using the Beneish M-Score model, with independent variables including pressure, opportunity, rationalization, ability, arrogance, and collusion, and the moderating variable of the Sharia Supervisory Board. The results show that pressure, opportunity, and rationalization have a significant effect on financial statement fraud, while ability, arrogance, and collusion have no effect. In addition, the Sharia Supervisory Board is able to moderate the influence of pressure and opportunity, but is not effective in moderating other variables. These findings emphasize the importance of the active role of the Sharia Supervisory Board in strengthening Islamic corporate governance. This study provides practical contributions to financial institutions and regulators to improve the effectiveness of internal supervision and prevent financial statement manipulation. Further studies are recommended to expand the scope of variables and explore qualitative approaches to enrich the understanding of the factors driving fraud in the Islamic financial system.